Structural, hardness and toughness evolution in Si-incorporated TaC films. Issue 8 (1st June 2018) - Du, Suxuan; Wen, Mao; Yang, Lina; Ren, Ping; Meng, Qingnan; Zhang, Kan; Zheng, Weitao
Abstract: Ta–Si-C films were deposited by DC magnetron co-sputtering using TaC and Si targets in an Ar-discharge atmosphere. Increasing the current of Si target from 0.0 to 0.5 A led to a continuous increase of Si content from 0.0 to 30.8 at%. The effects of Si content on microstructure were systematically investigated using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). At low Si content (≤ 5.6 at%), Si occupied C vacancies to form a solid solution Ta(C, Si). Further increasing the Si content, some Si atoms bonded with C atoms resulting in the formation of amorphous phase (a-C:Si), and the films presented a nanocomposite structure consisting of solid solution Ta(C, Si) surrounded by a-C:Si matrix. At the highest Si content (30.8 at%), the film exhibited finally X-ray amorphous structures. The hardness ( H ) and fracture toughness ( K f ) were observed to initially increase and then decrease as the Si content was increased. At 5.6 at% Si, the film exhibited a maximum in H (44.9 ± 2.7 GPa) and K f (3.61 ± 0.16 MPa m 1/2 ), which can be ascribed to the formation of a solid solution. On further increasing the Si content, an amorphous phase gradually appeared, leading to a decrease in H and K f .